Andexanet Alfa for Urgent Reversal of Apixaban Before Aortic Surgery Requiring Cardiopulmonary Bypass: A Case Report. Issue 7 (1st October 2019) - Flaherty, Devon; Connors, Jean M.; Singh, Steve; Sylvester, Katelyn W.; Rimsans, Jessica; Cornella, Lauren
Abstract : Andexanet alfa is a recombinant factor Xa decoy molecule capable of reversing direct and indirect factor Xa–inhibiting anticoagulants. We present an adult patient on apixaban for nonvalvular atrial fibrillation who required urgent reoperative aortic surgery for an aortic root pseudoaneurysm. Apixaban was reversed with andexanet alfa. A second dose of andexanet alfa was required before surgical incision for persistently elevated antifactor Xa levels. Intraoperative management required use of cardiopulmonary bypass (CPB). No major adverse cardiovascular, cerebrovascular, hemorrhagic, or thromboembolic events were observed.